All swamping, no problem. (26th December 2019) - Bjelde, Joseph
Abstract: The swamping problem is to explain why knowledge is epistemically better than true belief despite being no more true, if truth is the sole fundamental epistemic value. But Carter and Jarvis (2012) argue that the swamping thesis at the heart of the problem 'is problematic whether or not one thinks that truth is the sole epistemic good'. I offer a counterexample to this claim, in the form of a theory of epistemic value for which the swamping thesis is not problematic: evidence monism. Then I argue that another kind of response to the swamping problem given by Sylvan 2018 does not escape the problem unscathed, because it is not only instrumentalism that gives rise to the swamping problem. The upshot is that, given a standard account of fundamental value, the swamping problem favours evidence monism over truth monism.